Future Sea Level Rise Scenarios and the Shoreline of Mar del Plata, Argentina: Assessing Socioeconomic Impacts and Relief Measures - Celemin, Juan Pablo (2013)
This paper employs simulation models to gauge the effects of sea level rise (SLR) on the shoreline of Mar del Plata, Argentina, considering different scenarios. The analysis follows the findings and recommendations of the Intergovernmental Panel on Climate, as well as other relevant studies. We combine the information generated by the SLR simulation models with georeferenced census data to characterize the socioeconomic context were the impacts of SLR will take place, in order to help identify appropriate relief measures for the different sea level rise scenarios. Specifically, we attempt to answer the following questions: Where the coastal damage will take place? To what extent the effects of SLR will vary spatially? And, what is the present socioeconomic context of the areas in the city that will be most heavily exposed to SLR? The paper concludes with recommendations on relief measures.